Disruptive selling: a new approach to sales, marketing and customer service - Maes, Patrick (Koganpage, 2018)
The heyday of the classic sales force is over. Customers lead mobile and online lives, and successful companies use disruptive concepts to engage with the digitally empowered consumer. Disruptive Selling helps companies transform themselves to the new age of selling by matching supply to demand in an innovative way. Successful disruptive selling concepts must be based on the right combination of a series of factors, including an understanding of what motivates customers' corresponding value propositions, appropriate organizational structures, and the right overarching business culture. Disruptive Selling demystifies all of this, and more. Featuring case studies and examples from disruptive organizations such as AirBnB, Zalando and Bol.com, this book will empower readers to look critically at their organizations and commercial interaction models, and begin their own disruptive selling journeys. It contains a carefully researched, clearly explained framework to disruptive selling, and practical guidelines that will allow readers to get started immediately. Regardless of industry, sector or company-size, Disruptive Selling is the ultimate guide to remaining competitive and adaptive in a continually changing world.